C.O.W.L. Volume 2, The greater good - Higgins, Kyle, 1985-; Siegel, Alec (Image Comics, 2015)
With super villain threats a problem of the past, a strike on his hands, and scandal on the horizon, Geoffrey Warner has taken drastic steps to breathe life back into the Chicago Organized Workers League. But how far will his false-flag operation reach? Is there any line he won't cross for "the greater good?" Collects C.O.W.L. issues #7-11.